Spectrophotometric Estimation of Gatifloxacin inTablets - RAJESH,; SRIKANTH, (The journal of contemporary issues in business and government, 2020)
Gatifloxacin dosage forms may now be estimated using a simple, fast, accurate, and exact spectrophotometric approach. Due to the interaction of gatifloxacin with a ferric nitrate reagent solution, an orange-colored chromogen is formed that has a maximum absorption wavelength of 470 nm in comparison to blank. Up to one hour's stability was discovered in chromogen, which complied with linearity between 20 and 200 g/ml.